The Application of Religion as a Method of Drug Rehabilitation for Victims of Drug Abuse at Baitusyifa Rehabilitation Center - Nurul Adilla Alatas Abus; Arif Abdillah Lubis; Saffanah Qanitah HS; Crystin Manullang; Fajar Utama Ritonga (Tradition and Modernity of Humanity, 2024)
Drugs are a complex problem that needs to be resolved, one of the efforts that can be made is to undergo rehabilitation for drug abusers. Drug rehabilitation centers have different methods to achieve their clients' goals in the healing period. Baitusyifa Rehabilitation Center is one of the rehabilitation centers located in Deli Serdang City, North Sumatra which applies religion as a method of drug rehabilitation. The purpose of this study is to describe the religious methods or efforts applied at Baitusyifa Rehabilitation Center. This research uses a qualitative approach. Data were obtained through interviews, observations, and documentation at the research location. Furthermore, the data was analyzed using descriptive qualitative to answer the effectiveness of the application of religion in handling drug abuse clients. The results showed that the application of religion was very influential on clients at Baitusyifa Rehabilitation Center. Clients feel a change for the better and make habits that are carried out in rehabilitation to life after completing the rehabilitation period. Baitusyifa Rehabilitation Center takes an approach by creating self-awareness through study/recitation, changing habits with worship activities such as prayer and murojaah, increasing motivation through reward and punishment models, implementing anonymous letters so that clients evaluate themselves, cupping healing therapy recommended in Islam, and morning exercises to keep clients fit.